THE DIFFICULTIES OF UAE UNIVERSITY STUDENTS IN THE USE OF PREPOSITION - Al Murshidi, Ghadah (European Scientific Journal, ESJ, 2014)
Prepositions are functional words that present the relationships between groups of words. EFL students find difficulty in using prepositions correctly in their writing tasks. The present study is an attempt to identify the errors made by UAE University students in the Engineering College in the use of prepositions. The participants of the study are 30 Arabic students attending UAE University aged between 18 -23 years old. A test on English preposition was developed which contained thirty multiple choice questions, and distributed to the students. Errors have been pinpointed and results have been analyzed using discourse analysis. This study is expected to be valuable to EFL students, teachers and translators.